Student Management Strategies for Enhancing the Quality of Learning - Sirojul Munir, Ahmad; Ulfatin, Nurul (International Journal of Educational Research & Social Sciences, 2023)
This literature review delves into student management strategies as a key element in enhancing the quality of education. Strategies such as personalized curriculum implementation, participatory approaches in decision-making, and character development programs are central to creating a holistic learning environment. The management ofstudents is not merely administrative but includes strategies aimed at improving the qualityof learning and student development. However, the review also identifies challenges, including resistance to change, technical constraints, and unequal access to technology among students. Understanding and overcoming these challenges are crucial for the successful implementation of student management strategies. The review provides a foundation for improvement recommendations, including intensive training for education staff in technology application, character development programs, and strengthening participatory strategies. By addressing these recommendations, educational institutions have the opportunity to enhance their student management strategies, promote holistic student development, and improve the effectiveness of learning.